The α5-α6-α7-Pba3-Pba4 Complex: A Starting Unit in Proteasome Core Particle Assembly - Ana C. Matias; Margarida N. Tiago; Jessica Zimmermann; R. Jürgen Dohmen; Paula C. Ramos (Biomolecules)
A complex composed of Pba3-Pba4 and subunits α5, α6, and α7 is identified as an early intermediate in proteasome core particle assembly in wild-type Saccharomyces cerevisiae cells. The same complex can be reconstituted from recombinantly produced components in vitro. Assembly of α6 and α7 with Pba3-Pba4 depends on the presence of the α5 subunit, the binding of which apparently initiates the formation of this intermediate. Our data suggest the following order of events: first, Pba3-Pba4 binds α5, then α6 is incorporated, and at the end α7. In the absence of the chaperones Pba1-Pba2 or Ump1, alternative Pba4-containing complexes are detected, the formation of which depends on the Blm10/PA200 protein. Overexpression of Pba1-Pba2 abolishes the formation of these complexes containing Pba4 and Blm10, suggesting that Blm10 may replace Pba1-Pba2 as an alternative assembly factor.